Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk

Silk degumming and utilization of silk sericin by hydrolysis using alkaline protease from beauveria Sp. (MTCC 5184): a green approach - More, Snehal V.; Chavan, Sakalya; Prabhune, Asmita Ashutosh (Journal of Natural Fibers, 2017)
Conventionally, degumming is carried out at 90°C--110°C temperature by boiling the raw silk with Marseilles soap and sodium bicarbonate which eventually requires a lot of water and energy. In this study, degumming of Chinese bivoltine raw silk fibres with alkaline protease produced by Beauveria sp. (MTCC 5184) is studied. Complete degumming was obtained in 45 min with 75 units of enzyme per gram of silk. Degumming was found to be optimal at 50°C and pH 9.0. Scanning electron micrographs showed that the sericin deposits were removed and the obtained fibres were clean, separated, had smooth feel with shine as compared to untreated fibres. Sericin isolated from silk cocoon (by-product which goes waste) was hydrolyzed with the same alkaline protease obtained from Beauveria sp. to get small molecular weight peptides. These peptides can be utilized further for cosmetic, pharmaceutical, and various industrial applications.
Keywords: Alkaline Protease; bivoltine; degumming; Silk; weight loss